2016
DOI: 10.1016/j.toxicon.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Who knows not where an anemone does wear his sting? Could polypeptides released from the columnar vesicles of Bunodosoma cangicum induce apoptosis in the ZF-L cell line?

Abstract: We provide ultrastructural and cytological evidence that the tentacles of the sea anemone Bunodosoma cangicum does not contain cytotoxic venom. However, we show that the stimulated secretion of an apparent mixture of biomolecules containing polypeptides from the columnar vesicles of Bunodosoma cangicum is apparently a potent inducer of apoptosis in the zebrafish cell line, ZF-L. Microscopic fluorescence, cell morphology and flow cytometric assays confirm the apoptotic activity. Crude vesicle venom was partiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Our group has previously identified that the active compounds of the crude venom are in the low weight fraction (Bastos et al, 2016). The column was mounted in a 10 mL syringe and equilibrated with deionized water at room temperature.…”
Section: Gel-filtration Chromatographymentioning
confidence: 99%
See 4 more Smart Citations
“…Our group has previously identified that the active compounds of the crude venom are in the low weight fraction (Bastos et al, 2016). The column was mounted in a 10 mL syringe and equilibrated with deionized water at room temperature.…”
Section: Gel-filtration Chromatographymentioning
confidence: 99%
“…Anemone venom extracts, for example, have been identified with nephrotoxic, neurotoxic, hemolytic, apoptotic, and channel blocking activities (Bosmans and Tytgat, 2007;Beeton et al, 2011;Nedosyko et al, 2014;Ramezanpour et al, 2014b;Bastos et al, 2016). A general feature of Cnidaria are the presence of cnidocytes of different types, located in different regions of the body, but usually concentrated in the catch tentacles.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations